Synthesis of Multisubstituted Indenes via Iron-Catalyzed Domino Reaction of Benzylic Compounds and Alkynes - Chen, Yongxin; Li, Kangning; Liu, Xiang; Zhu, Jiaoyan; Chen, Baohua (Synlett, 2013)
A novel approach to synthesizing multisubstituted indenes by iron-catalyzed domino reaction of benzylic compounds and alkynes under mild conditions was developed. This system could be applied to various available substrates in a one-step synthetic procedure in moderate to good yields.
Keywords: indenes; iron catalysis; domino reaction; one-step procedure; annulation